ПСИХОЛОГО-ПЕДАГОГИЧЕСКАЯ КОРРЕКЦИЯ ЭМОЦИОНАЛЬНО-ВОЛЕВОЙ СФЕРЫ ПОДРОСТКОВ С ЦИФРОВОЙ ЗАВИСИМОСТЬЮ - Абдрахманов , А.Э.; Тарасенко, Е.Б. (Вестник КазНПУ имени Абая. Серия: Психология, 2022)
The article reveals the results of an experimental study on the search for effective ways to correct the emotional and volitional sphere of adolescent students with digital addiction. The analysis of modern research on the problem of psychological diagnosis and correction of Internet addictions in adolescents is carried out. A model of psychological and pedagogical correction and development of the emotional and volitional sphere of adolescent students as the basis for the prevention of digital addiction is presented. On a sample of adolescents with digital addiction and the risk of its formation, the features of such indicators of the emotional-volitional sphere as emotional intelligence, anxiety, and volitional regulation of behavior were studied. The program of psychological and pedagogical correction, based on an integrative approach, included a variety of forms and methods of work: psychotechnical exercises, conversations, mini-lectures, discussions, problem situations, autogenic training method, role-playing games, essays, training/ Using the methods of mathematical statistics, it was found that the implementation of the program of psycho-correction of the emotional-volitional sphere helps to reduce the level of digital addiction. Recommendations for the correction and development of the emotional-volitional sphere and the prevention of digital addiction are proposed.